2018
DOI: 10.3847/1538-4357/aaa080
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-corrected Herschel Observations of Nearby Isolated Low-mass Clouds*

Abstract: We present intensity-corrected Herschel maps at 100 µm, 160 µm, 250 µm, 350 µm, and 500 µm for 56 isolated low-mass clouds. We determine the zero-point corrections for Herschel PACS and SPIRE maps from the Herschel Science Archive (HSA) using Planck data. Since these HSA maps are small, we cannot correct them using typical methods. Here, we introduce a technique to measure the zero-point corrections for small Herschel maps. We use radial profiles to identify offsets between the observed HSA intensities and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 107 publications
2
26
4
Order By: Relevance
“…The millimeter imaging of Launhardt & Sargent (2001) identified a deeply embedded, ∼0.3 M e protostar with an edge-on disk forming within L1439. These authors suggested the cloud may be an extension of the Taurus-Auriga star-forming region (see also Sadavoy et al 2018).…”
Section: Isolated Star Formation In the L1438 Molecular Cloudmentioning
confidence: 97%
“…The millimeter imaging of Launhardt & Sargent (2001) identified a deeply embedded, ∼0.3 M e protostar with an edge-on disk forming within L1439. These authors suggested the cloud may be an extension of the Taurus-Auriga star-forming region (see also Sadavoy et al 2018).…”
Section: Isolated Star Formation In the L1438 Molecular Cloudmentioning
confidence: 97%
“…To determine the basic physical properties of the BHR 71 core, we used the FIR data taken by the Herschel satellite. Sadavoy et al (2018) provided an intensity-corrected Herschel map of BHR 71, and a map at an optical depth of 353 GHz (τ 353GHz ) was included in their products. The map has 28 × 28 pixels with a pixel scale of 14 ′′ pixel −1 and resolution of 36.3 ′′ .…”
Section: Distortion Of Magnetic Fieldsmentioning
confidence: 99%
“…We started with the extended source map and utilized the tabulated beam correction, color correction, and aperture correction for a source with a spectral index of 3.5 and a temperature of 30 K. These are reasonable assumptions for a protostar as the SED peaks at ∼100 µm and the dust opacity spectral index will result in a spectral index between 3 and 4 in the sub-millimeter range. Our photometry are taken toward the region of compact emission toward the protostar locations and not from the entire extended core; thus, we do not need to worry about the proper zero-point flux calibration as in (Sadavoy et al 2018) 3. OBSERVATIONAL RESULTS The multitude of infrared and submillimeter data taken toward BHR71 are shown in Figures 1 & 2.…”
Section: Herschel Observations and Photometrymentioning
confidence: 99%
“…With these values, we estimate the Jeans length to be ∼8400 AU, which is much larger than the projected separation of IRS1 and IRS2. Lower temperatures were certainly possible prior to protostar formation (e.g., Stutz et al 2010;Sadavoy et al 2018) and higher densities as well, but an average density 10× higher is necessary to make the Jeans length comparable to the current protostar separation. Thus, thermal Jeans fragmentation is not clearly a favored mechanism on its own to form the binary system, and turbulent fragmentation remains the most likely candidate.…”
Section: Formation Of the Binary Systemmentioning
confidence: 99%